Comparative proteomic analysis of antagonistic Bacillus amyloliquefaciens Q‐426 cultivated under different pH conditions. (26th December 2014) - Zhao, Jing; Zhao, Pengchao; Quan, Chunshan; Jin, Liming; Zheng, Wei; Fan, Shengdi
Abstract Bacillus amyloliquefaciens Q‐426 produces lipopeptide compounds with antifungal activities. Initial pH value has a significant influence on the production of lipopeptide compounds. The correlation between pH and intrinsic mechanism of lipopeptide production was rarely discussed. In this research, comparative proteomics, using two‐dimensional gel electrophoresis and mass spectrometry, was applied to identify B. amyloliquefaciens Q‐426 intracellular proteins differentially expressed under initial pH 5.0 and 7.3. A total of 24 differential spots (eight downregulated and 16 upregulated) under pH 5.0 were identified. Certain proteins were involved in the regulation of bacillomycin and fengycin production by B. amyloliquefaciens Q‐426. These proteins include four induced proteins related to stress response: Thiamine pyrophosphate‐dependent acetoin dehydrogenase, butanediol dehydrogenase, two ABC‐type oligopeptide transport system proteins, and two‐component response regulator DegU and chorismate mutase PheB. These results indicate intrinsic differences of antagonistic B. amyloliquefaciens Q‐426 under different pH conditions.